Virtual Reality for Surgical Planning – Evaluation Based on Two Liver Tumor Resections - Reinschluessel, Anke V.; Muender, Thomas; Salzmann, Daniela; Döring, Tanja; Malaka, Rainer; Weyhe, Dirk (Frontiers in Surgery, 2022)
Purpose. For complex cases, preoperative surgical planning is a standard procedure to ensure patient safety and keep the surgery time to a minimum. Based on the available information, such as MRI or CT images, and prior anatomical knowledge the surgeons create their own mental 3D model of the organ of interest. This is challenging, requires years of training and an inherent uncertainty remains even for experienced surgeons. Goal. Virtual reality (VR) is by nature excellent in showing spatial relationships through its stereoscopic displays. Therefore it is well suited to be used to support the understanding of individual anatomy of patient-specific 3D organ models generated from MRI/CT data. Utilising this potential, we developed a VR surgical planning tool that provides a 3D view of the medical data for better spatial understanding as well as natural interaction with the data in 3D space. Following a user-centred design process, in this first user study, we focus on usability, usefulness and target audience feedback. Thereby, we also investigate the individual impact the tool and the 3D presentation of the organ have on the understanding of the 3D structures for the surgical team. Methods. We employed the VR prototype for surgical planning using a standard VR setup to two real cases of patients with liver tumours who were scheduled for surgery at a University Hospital for Visceral Surgery. Surgeons (N=4) used the VR prototype before the surgery to plan the procedure in addition to their regular planning process. We used semi-structured interviews before and after the surgery to explore the benefits and pitfalls of VR surgical planning. Results. The participants used on average 14.3 minutes (SD = 3.59) to plan the cases in VR. The reported usability was good. Results from the interviews and observations suggest that planning in VR can be very beneficial for surgeons. They reported an improved spatial understanding of the individual anatomical structures and better identification of anatomical variants. Additionally, as the surgeons mentioned an improved recall of the information and better identification of surgical relevant structures, the VR tool has the potential to improve the surgery and patient safety.